2018
DOI: 10.13181/mji.v26i4.1623
|View full text |Cite
|
Sign up to set email alerts
|

Association between varicocele grade and semen analysis parameter

Abstract: Background: Varicocele is a condition characterized by elongation, dilatation and tortuousity of spermatic vein in pampiniform plexus. Approximately 50% of infertility cases among men are caused by varicocele. The varicocele may affect the components of sperm. This study aimed to determine the association between varicocele grade based on ultrasound Doppler examination and sperm concentration, sperm motility, and sperm morphology based on semen analysis examination.Methods: This was a descriptive, cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Varicoceles are graded based on physical examination, with grades 1, 2 and 3 varicoceles defined as palpable only by Valsalva, palpable without Valsalva and visible on examination respectively. The relationship between varicocele grade and degree of disturbance to semen parameters is controversial, although multiple studies have shown a significant correlation between increasing grade and semen analysis abnormalities, as well as lower testosterone levels (Al-Ali, Shamloul, Pichler, Augustin, & Pummer, 2013;Ariyati, Mulyadi, Birowo, Wiweko, & Prihartono, 2018). In a prospective study comparing men with varicoceles to normozoospermic controls, stratification by grade revealed a significantly higher percentage of men with normal semen parameters in those with grade I (50%) versus grade III (24%) varicoceles (Vivas-Acevedo, Lozano, & Camejo, 2010).…”
Section: Semen Analysis and Varicocele Gradingmentioning
confidence: 99%
“…Varicoceles are graded based on physical examination, with grades 1, 2 and 3 varicoceles defined as palpable only by Valsalva, palpable without Valsalva and visible on examination respectively. The relationship between varicocele grade and degree of disturbance to semen parameters is controversial, although multiple studies have shown a significant correlation between increasing grade and semen analysis abnormalities, as well as lower testosterone levels (Al-Ali, Shamloul, Pichler, Augustin, & Pummer, 2013;Ariyati, Mulyadi, Birowo, Wiweko, & Prihartono, 2018). In a prospective study comparing men with varicoceles to normozoospermic controls, stratification by grade revealed a significantly higher percentage of men with normal semen parameters in those with grade I (50%) versus grade III (24%) varicoceles (Vivas-Acevedo, Lozano, & Camejo, 2010).…”
Section: Semen Analysis and Varicocele Gradingmentioning
confidence: 99%